CD49f protein expression varies among genetic subgroups of B lymphoblastic leukemia and is distinctly low in KMT2A‐rearranged cases. Issue 2 (2nd January 2020) - Collins, Katrina; Cardinali, Jolene L.; Mnayer, Laila O.; DiGiuseppe, Joseph A.
Abstract: Background: CD49f (integrin α6) is a useful marker for minimal residual disease (MRD) detection in B lymphoblastic leukemia and has recently been suggested to mediate infiltration of the central nervous system by leukemic B lymphoblasts. However, data regarding expression of CD49f protein in B lymphoblastic leukemia are limited, and whether CD49f protein expression varies among genetic subgroups of B lymphoblastic leukemia is unknown. Methods: CD49f protein expression was characterized by flow cytometry in a series of 40 cases of B lymphoblastic leukemia, which included the genetic subgroups: KMT2A ‐rerranged, BCR‐ABL1 +, ETV6‐RUNX1 +, hypodiploidy, and hyperdiploidy. Results: Expression of CD49f differed significantly among the five genetic subgroups studied, whether assessed by percentage of blasts positive for the antigen ( p = .0001, Kruskal–Wallis) or median fluorescence intensity (MFI) ( p = .0001, Kruskal‐Wallis). Moreover, the percentage of CD49f+ blasts and MFI of CD49f were significantly lower in KMT2A ‐rearranged cases than in cases without KMT2A rearrangement ( p = .0002 for both, Mann–Whitney). Conclusions: CD49f protein expression varies among genetic subgroups of B lymphoblastic leukemia, and is distinctly low in KMT2A ‐rearranged cases.